2017
DOI: 10.1093/ijnp/pyx005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal-Regulated Kinases (ERK 1/2) in the Locus Coeruleus Contributes to Pain-Related Anxiety in Arthritic Male Rats

Abstract: Background:There is increasing evidence suggesting that the Locus Coeruleus plays a role in pain-related anxiety. Indeed, we previously found that prolonged arthritis produces anxiety-like behavior in rats, along with enhanced expression of phosphorylated extracellular signal-regulated kinase 1/2 (a marker of plasticity) in the Locus Coeruleus. However, it is unknown how this effect correlates with the electrophysiological activity of Locus Coeruleus neurons or pain-related anxiety.Methods:Using the complete F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(70 reference statements)
3
17
0
Order By: Relevance
“…In the anxiogenic conditions, a large number of protein kinase cascades will be activated and responsible for various functions, including neurotransmitter release and receptor binding. Among the cascade of events, activation of ERK ½ (extracellular signal‐regulated kinases) is one of the important causes of hyperactivation of neurons in anxiety . In the present study, supplementation of TCHE had up‐regulated ERK ½ and p‐ERK ½ in a dose‐dependent manner when compared to PTX group.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the anxiogenic conditions, a large number of protein kinase cascades will be activated and responsible for various functions, including neurotransmitter release and receptor binding. Among the cascade of events, activation of ERK ½ (extracellular signal‐regulated kinases) is one of the important causes of hyperactivation of neurons in anxiety . In the present study, supplementation of TCHE had up‐regulated ERK ½ and p‐ERK ½ in a dose‐dependent manner when compared to PTX group.…”
Section: Discussionsupporting
confidence: 49%
“…Among the cascade of events, activation of ERK ½ (extracellular signal-regulated kinases) is one of the important causes of hyperactivation of neurons in anxiety. [48] In the present study, supplementation of TCHE had up-regulated ERK ½ and p-ERK ½ in a dose-dependent manner when compared to PTX group. Tannins of TCHE may exert a significant anxiolytic effects by binding to GABA site and enhancing monoaminergic neurotransmission.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, the control of pain implies several molecular changes at the spinal cord, in the descending modulation of pain, and in supraspinal areas involved in the emotional component of pain processing [4,5,7,[9][10][11]. The latter may be influenced and altered by the noxious stimuli and also may be responsible for changes in the way these pathologic stimuli are processed [9,12,13]. Despite this knowledge, much is still unclear about how and when these changes in pain processing occur during the progression of a chronic joint inflammatory painful condition.…”
mentioning
confidence: 99%
“…Thus, while DNIC studies indicate that these circuits might be compromised, a thorough evaluation of the descending noradrenergic system is still needed in joint inflammatory pain.The main spinal source of noradrenaline is the Locus coeruleus (LC), which presents a functional dichotomy, by modulating descending inhibition through its projections to the spinal cord, and by mediating emotional-related behaviors via its ascending targets [9,27]. Through these LC projections to brain regions implicated in the affective component of pain, such as the anterior cingulate cortex (ACC) and the amygdala, a noradrenergic impairment might be implicated on the onset of pain-induced emotional disorders [9,10,12]. Interestingly, Borges et al have shown that, in the CFA monoarthritis model, the expression of the phosphorylated extracellular signal-regulated kinases 1 and 2 (pERKs1/2), a neuronal activation marker, was increased in the LC, as well as in ACC and amygdala at 28 days of MA, and this was concomitant with the onset of emotional behavioral comorbidities [9,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation